Knock-down of hypoxia-induced carbonic anhydrases IX and XII radiosensitizes tumor cells by increasing intracellular acidosis - Doyen, Jérôme; Parks, Scott K.; Marcié, Serge; Pouysségur, Jacques; Chiche, Johanna (Frontiers in Oncology, 2013)
The relationship between acidosis within the tumor microenvironment and radioresistance of hypoxic tumor cells remains unclear. Previously we reported that hypoxia-induced carbonic anhydrases CAIX and CAXII constitute a robust pHi-regulating system that confers a survival advantage on hypoxic human colon carcinoma LS174Tr cells in acidic microenvironments. Here we investigate the role of acidosis, CAIX and CAXII knock-down in combination with ionizing radiation. Fibroblasts cells (-/+ CAIX) and LS174Tr cells (inducible knock-down for ca9/ca12) were analyzed for cell cycle phase distribution and survival after irradiation in extracellular pHo manipulations and hypoxia (1% O2) exposure. Radiotherapy was used to target ca9/ca12-silenced LS174Tr tumors grown in nude mice. We found that diminishing the pHi-regulating capacity of fibroblasts through inhibition of NHE-1 sensitize cells to radiation-induced cell death. Secondly, the pHi-regulating function of CAIX plays a key protective role in irradiated fibroblasts in an acidic environment as accompanied by a reduced number of cells in the radiosensitive phases of the cell cycle. Thirdly, we demonstrate that irradiation of LS174Tr spheroids, silenced for either ca9 or both ca9/ca12, showed a respective 50% and 75% increase in cell death as a result of a decrease in cell number in the radioresistant S phase and a disruption of CA-mediated pHi regulation. Finally, LS174Tr tumor progression was strongly decreased when ca9/ca12 silencing was combined with irradiation in vivo. These findings highlight the combinatory use of radiotherapy with targeting of the pHi-regulating carbonic anhydrases as an anti-cancer strategy.